Representations of mother-son relationships in late-medieval English miscellanies, c. 1300 – c. 1500 - Sisson, Lauren Michele (2024)
Scholarship on medieval mothers and motherhood has gained momentum since the formative works of Clarissa Atkinson, and Bonnie Wheeler and John Carmi Parsons. The significance of mothers and motherhood in the society and culture of the Medieval world is now more widely understood. However, literary portrayals of mother-son relationships remain relatively unexplored, despite their ubiquity. This thesis explores representations of mother-son relationships in a range of texts found in a sample of Middle English miscellanies, dating c. 1300 to c. 1500, setting textual analysis alongside social and cultural historical contexts. The Auchinleck manuscript, the London and Lincoln Thornton manuscripts, and the Heege manuscript are important collections of Middle English literature, and represent a wide chronological and social span.